Comparative Analyisis of Software Cost Estimation Project using Algorithmic Method - Muhammad Indra Zul Aqlani; Nuning Septiana (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2018)
Software Cost Estimation has become an important factor to determine the efficiency of software development. There are many model of cost estimation like algorithmic model, top-down, and expert judgement. From all those models, Development in Algorithmic model is higher than the others. In this paper we present a comparative analysis of software cost project using algorithmic methods.